2022
DOI: 10.3390/ijerph192416905
|View full text |Cite
|
Sign up to set email alerts
|

The Third Half: A Pilot Study Using Evidence-Based Psychological Strategies to Promote Well-Being among Doctoral Students

Abstract: Over the last few years, various studies have reported decreasing well-being levels among doctoral students, who show a higher risk of suffering from psychological distress than the general population. Accordingly, European policies in higher education encourage well-being promotion programs among doctoral studies to enhance young researchers’ well-being. However, programs using evidence-based practices for well-being promotion are not yet generalised in public universities. The present study describes a pilot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…In [64], gamified sport practices were considered as being crucial for the development and activation of executive functions. This idea is shared with [70][71][72], in which it was stated that the relevance of executive functions in the establishment and preservation of physical and mental health to face risk factors such as stress, sleep disturbances, loneliness, or lack of exercise affects the development of these functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [64], gamified sport practices were considered as being crucial for the development and activation of executive functions. This idea is shared with [70][71][72], in which it was stated that the relevance of executive functions in the establishment and preservation of physical and mental health to face risk factors such as stress, sleep disturbances, loneliness, or lack of exercise affects the development of these functions.…”
Section: Discussionmentioning
confidence: 99%
“…The authors of [57,61,62,68,72] found that physical activity produces mental well-being. The same opinion was detailed in [26] regarding exergames, and this was due to the fact that this type of game decreases levels of stress.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies focusing on university students found that perceived greenness, UGSs, or academic GSs help them reduce feelings of anxiety, depression, and uncertainty or, conversely, promote psychological rehabilitation and academic performance [34,72,87,[171][172][173][174][175][176][177][178][179][180][181][182]. This has become even more apparent following the COVID-19 pandemic lockdowns that were implemented on a global level.…”
Section: Discussionmentioning
confidence: 99%
“…La investigación contribuye a comprender cómo se pueden construir aplicaciones de salud mental autoguiadas y cómo las utilizan los participantes Muro et al (34) , 2022 Implementar y evaluar una experiencia piloto de promoción del bienestar y prevención de la salud mental utilizando un enfoque multicomponente de estrategias psicológicas basadas en evidencia entre estudios de doctorado.…”
Section: Desarrollounclassified